A dialogue based mobile virtual assistant for tourists: The SpaceBook Project. (January 2018) - Bartie, Phil; Mackaness, William; Lemon, Oliver; Dalmas, Tiphaine; Janarthanam, Srini; Hill, Robin L.; Dickinson, Anna; Liu, Xingkun
Abstract: Ubiquitous mobile computing offers innovative approaches in the delivery of information that can facilitate free roaming of the city, informing and guiding the tourist as the city unfolds before them. However making frequent visual reference to mobile devices can be distracting, the user having to interact via a small screen thus disrupting the explorative experience. This research reports on an EU funded project, SpaceBook, that explored the utility of a hands-free, eyes-free virtual tour guide, that could answer questions through a spoken dialogue user interface and notify the user of interesting features in view while guiding the tourist to various destinations. Visibility modelling was carried out in real-time based on a LiDAR sourced digital surface model, fused with a variety of map and crowd sourced datasets (e.g. Ordnance Survey, OpenStreetMap, Flickr, Foursquare) to establish the most interesting landmarks visible from the user's location at any given moment. A number of variations of the SpaceBook system were trialled in Edinburgh (Scotland). The research highlighted the pleasure derived from this novel form of interaction and revealed the complexity of prioritising route guidance instruction alongside identification, description and embellishment of landmark information – there being a delicate balance between the level of information 'pushed' to the user, and the user's requests for further information. Among a number of challenges, were issues regarding the fidelity of spatial data and positioning information required for pedestrian based systems – the pedestrian having much greater freedom of movement than vehicles. Highlights: Near realtime viewshed based on LiDAR to calculate urban objects in view Location aware spoken dialogue system for pedestrians Pedestrian navigation system with realtime map matching to improve positioning Hands-free, eyes-free interface – only using speech user interface for all tasks.